Problems in applying the curriculum of art education in villages and remote areas from the teachers‘ point of view - Al Shabanat, Sarah Bint Nasser Bin Sulaiman (Journal of Educational and Psychological Sciences, 2019)
The objective of the research to identify the problems of applying the curriculum of art education developed in villages and remote areas from the point of view of parameters. The descriptive approach has been used, where the study population is one of the teachers of art education in villages and remote areas (34) teachers. The technical education room is not equipped with suitable equipment for the application of the curriculum of advanced art education such as ceramic ovens, washing machine washing tools, etc., the inability of the student to be able to From the provision of tools and raw materials to the absence of libraries in the villages, the absence of a teacher for the distance of residence from the village headquarters and the lack of appropriate educational activities in the curriculum of art education developed for the physical potential of the school environment. The most important recommendations are: Providing a special bag for girls from remote villages and areas containing all necessary to apply the curriculum of art education to take into account their economic circumstances. Holding training courses for teachers of art education on the developed curriculum and how to teach it and adapt it to the rural environment and how to find alternatives to tools from the local environment. Developed as a pilot phase in villages and remote areas and include the curriculum with free educational activities; chosen by the teacher in proportion to the environment and nature of students.
Keywords: school equipment; developed curriculum; rural environment; school